2020 MR Safety for Cardiac Devices: An Update for Radiologists. Issue 4 (November 2021) - Lebel, Kiana; Mondesert, Blandine; Robillard, Julie; Pham, Magali; Terrone, Donato; Tan, Stephanie
Magnetic resonance imaging (MRI) is a unique and powerful diagnostic tool that provides images without ionizing radiation and, at times, can be the only modality to properly assess and diagnose some pathologies. Although many patients will need an MRI in their lifetime, many of them are still being unjustly denied access to it due to what were once considered absolute contraindications, including MR nonconditional pacemakers and implantable cardioverter-defibrillators. However, there are a number of large studies that have recently demonstrated that MRI can safely be performed in these patients under certain conditions. In addition, there are an increasing number of novel cardiac devices implanted in patients who may require an MRI. Radiologists need to familiarize themselves with these devices, identify which patients with these devices can safely undergo MRI, and under which conditions. In this article, we will review the current literature on MR safety and cardiac devices, elaborate on how to safely image patients with cardiac devices, and share the expertise of our tertiary cardiac institute.